Pengalaman Keberagamaan Ibu Miskin Meninggalkan Gereja Pada Buku “Living Faith: Everyday Religion And Mothers In Poverty” - Najihah, Bannan Naelin; Truna, Dody S (Universitas Islam Negeri Raden Intan Lampung, 2023)
This research reveals the causes and religious experiences of poor single mothers leaving the church in the book